O trabalho da terra: as implicações da mercantilização da agricultura e da migração compulsória - o caso do Reassentamento Cristo Rei/RS (1970-2010) - Juriatti, Tamara (2023)
The present work seeks to understand the implications of the transformations in the agricultural work of a group of male and female farmers after the changes caused by the growing agricultural commercialization that began in the 1970s. The group studied lives in the rural area, in the Reassentamento Cristo Rei, in the Municipality of Chiapetta/RS. Through the use of interviews with farmers, IBGE's agricultural census, photographs, rural producer invoice books, and bibliographies, it was possible to trace a trajectory of the way of living and working of the farming families over five decades, noting substantial changes in production for self-consumption and for commercialization. As the main points of dynamism, we can mention that the commercialization of the means of work, together with other factors, implied many changes, such as the increase in the circuit of commercial relations of the families, specialization of production in some products, and the liberation of part of the labor force. Compulsory migration, even though it took place to a relatively nearby city, brought a new geographical and productive reality, which accelerated the process of mercantilization. Allied to this, provided access to more means of consumption, and caused a rearrangement in the networks of sociability. All the perceived processes reflect a reality of family agriculture in the Northern Region of Rio Grande do Sul, with agrarian conflicts and an escalating rise of agribusiness, which has created what was conceptualized as family work integrated and subordinated to agribusinesses, which changes some traditional precepts of these families, but that even so tries to maintain their way of life, guaranteeing family reproduction and the diversity of the Brazilian agrarian environment.